AVENUE21. Planning and Policy Considerations for an Age of Automated Mobility - Mitteregger, Mathias; Bruck, Emilia M.; Soteropoulos, Aggelos; Stickler, Andrea; Berger, Martin; Dangschat, Jens S.; Scheuvens, Rudolf; Banerjee, Ian (Springer Nature, 2023)
The subject of this open-access publication is the impact of connected and automated vehicles on the European city and the conditions under which this technology can make a positive contribution to urban development. The authors put forward two theses that have received little attention in the scientific discourse so far: Connected and automated vehicles will not become fully established in all sub-areas of the city for a long time. As a result, previously assumed effects - from traffic safety to traffic performance as well as spatial effects - will have to be reevaluated. To ensure a positive contribution of this technology to the mobility of the future, transport and settlement policy regulations must be further developed. Established territorial, institutional and organizational boundaries need to be challenged in a timely manner. Despite or because of the existing great uncertainties, we are at the beginning of a phase of yet shaping the possible future - in technology development, but also in politics, urban planning, administration and civil society. Description of the chapters: 1. Connected and automated driving: The long level 4 Mathias Mitteregger reflects on the road ahead for automated driving. What pathways of technological development induce which kind of spatial effects and planning needs? 2. Connected and automated driving: Consideration of the local, spatial context and spatial differentiation Emilia M. Bruck and Aggelos Soteropoulos reflect on the importance of the local context when classifying and estimating the effects of different forms of automated mobility. 3. Connected and automated driving in the context of a sustainable transport and mobility transformation Andrea Stickler, Jens S. Dangschat and Ian Banerjee integrate possible potentials of automated mobility in the context of a transformed, sustainable transport system. PART I: Mobility and transport 4. Self-driving turnaround or automotive continuity? Reflections on technology, innovation and social change Katharina Manderscheid reflects on how differing visions of an automated future can be understood with regard to divergent interests in technological development. 5. Automated drivability and streetscape compatibility in the urban-rural continuum using the example of Greater Vienna Aggelos Soteropoulos analyses how different street spaces align with technological requirements of automated mobility, creating a suitability framework for road spaces in the Greater Vienna region. 6. Automation, public transport and Mobility as a Service: Experience from tests with automated shuttle buses The authors show what types of automated public transport might be used in the future and what can be learned from testing automated shuttle buses in the past. 7. Delivery robots as a solution for the last mile in the city? Bert Leerkamp, Aggelos Soteropoulos and Martin Berger describe how automated delivery robots could be contextualized in terms of solving last-mile problems and discuss what implications might lie ahead for urban planning. PART II: Public space 8. Control and design of spatial mobility interfaces The authors identify the possible implications of automated mobility for mobility interfaces and explore how public spaces could be transformed. 9. Transformations of European public spaces with AVs Robert Martin, Emilia M. Bruck and Aggelos Soteropoulos use the example of Copenhagen to show how public spaces could be transformed in an age of automated urban mobility and benefit from lower car dependency. 10. At the end of the road: Total safety Mathias Mitteregger discusses how the desire for road safety affects public spaces and how automated mobility influences this discourse. 11. Integration of cycling into future urban transport structures with connected and automated vehicles Looking at the future of mobility, Lutz Eichholz and Detlef Kurth show that the bike actually offers solutions to many of our current problems and that planning should not forget to integrate cycling into future urban transport structures and systems. 12. Against the driverless city Steven Fleming argues for a radical shift in cities towards a highly improved cycling infrastructure eradicating the need for automated mobility. Part III: Spatial development 13. Strategic spatial planning, "smart shrinking" and the deployment of CAVs in rural Japan Ian Banerjee and Tomoyuki Furutani show where automated mobility could help tackle pressing issues in rural Japan. 14. Integrated strategic planning approaches to automated transport in the context of the mobility transformation The authors show how new forms of automated mobility could be integrated into mobility systems in diverse spatial structures in the city region of Vienna with the overriding goal of the mobility transformation. 15. Opportunities from past mistakes: Land potential en route to an automated mobility system Looking at the mistakes made in building a car-centric environment in the past, Mathias Mitteregger and Aggelos Soteropoulos identify future areas of urban transformation as a result of a lower demand for car-centric infrastructures and businesses. Part IV: Governance 16. New governance concepts for digitalization: Challenges and potentials Alexander Hamedinger contextualizes the manifold paths towards an automated future with regard to governance and describes how governance concepts might need to adapt in the future. 17. How are automated vehicles driving spatial development in Switzerland? Fabienne Perret and Christof Abegg show how automated vehicles are influencing spatial development in Switzerland, focusing on three different scenarios on the road ahead. 18. Lessons from local transport transition projects for connected and automated transport Andrea Stickler looks at local projects aiming at a transformation of mobility practices and reflects on implications for automated transport. 19. Connected and automated transport in the socio-technical transition Jens S. Dangschat looks at societal transformations in the past and contextualizes automated mobility in terms of a possible socio-technical transition ahead. 20. Data-driven urbanism, digital platforms and the planning of MaaS in times of deep uncertainty: What does it mean for CAVs? Ian Banerjee, Peraphan Jittrapirom and Jens S. Dangschat show how continuous digitalization in cities might affect possible uses and implementations of CAVs and their accompanying systems.